Design, Synthesis and Biological Evaluation of Novel N-hydroxyheptanamides Incorporating 6-hydroxy-2-methylquinazolin-4(3H)-ones as Histone Deacetylase Inhibitors and Cytotoxic Agents - Minh, Nguyen V.; Thanh, Nguyen T.; Lien, Hoang T.; Anh, Dinh T.P.; Cuong, Ho D.; Nam, Nguyen H.; Hai, Pham T.; Minh-Ngoc, Le; Le-Thi-Thu, Huong; Chinh, Luu V.; Vu, Tran K. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Target-based approach to drug discovery currently attracts a great deal of interest from medicinal chemists in anticancer drug discovery and development worldwide, and Histone Deacetylase (HDAC) inhibitors represent an extensive class of targeted anti-cancer agents. Among the most explored structure moieties, hydroxybenzamides and hydroxypropenamides have been demonstrated to have potential HDAC inhibitory effects. Several compounds of these structural classes have been approved for clinical uses to treat different types of cancer, such as vorinostat and belinostat. Aims: This study aims at developing novel HDAC inhibitors bearing quinazolinone scaffolds with potential cytotoxicity against different cancer cell lines. Methods: A series of novel N-hydroxyheptanamides incorporating 6-hydroxy-2 methylquinazolin-4(3H)-ones (14a-m) was designed, synthesized and evaluated for HDAC inhibitory potency as well as cytotoxicity against three human cancer cell lines, including HepG-2 (liver cancer), MCF-7 (breast cancer) and SKLu-1 (lung cancer). Molecular simulations were finally carried out to gain more insight into the structure-activity relationships. ADME-T predictions for selected compounds were also performed to predict some important features contributing to the absorption profile of the present hydroxamic derivatives. Results: It was found that the N-hydroxyheptanamide 14i and 14j were the most potent, both in terms of HDAC inhibition and cytotoxicity. These compounds displayed up to 21-71-fold more potent than SAHA (suberoylanilide hydroxamic acid, vorinostat) in terms of cytotoxicity, and strong inhibition against the whole cell HDAC enzymes with IC50 values of 7.07-9.24μM. Docking experiments on HDAC2 isozyme using Autodock Vina showed all compounds bound to HDAC2 with relatively higher affinities (from -7.02 to -11.23 kcal/mol) compared to SAHA (-7.4 kcal/mol). It was also found in this research that most of the target compounds seemed to be more cytotoxic toward breast cancer cells (MCF-7) than liver (HepG2), and lung (SKLu-1) cancer cells.
Keywords: Nhydroxyheptanamide